KINETIC STUDY OF REDUCTION OF’ Bis(PENTANE-2,4-DIONATo) DIAQUO MANGANESE (III) COMPLEX WITH SODIUM TmoSULPHATE: Short Communication - Farrukh, M Akhyar; Naqvi, lftikhar Imam (Biological Sciences - PJSIR, 2002)
Kinetics of several oxidation-reduction reactions pertaining to manganese have been reported but very few of them in volve manganese (III) in perchloric acid. This may be because free manganic ions can not exist in significant con centration in aqueous solutions. Manganese (III) forms a number of complexes with fluoride, chloride, phosphate, pyrophosphate, sulphate,porphyrin, heteropoly anions (Baker 1961;Brauer 1963; Kemmit 1973)